Comparative Analysis of Clinical and Laboratory Parameters and Assessment of Antiretroviral Therapy Effectiveness in HIV-Associated Cryptococcal Meningoencephalitis in the Case of Immune Inflammation Syndrome - D.A. Mustafaeva1, L.N. Tuychiev2, E.I. Musabaev3, T.S. Zaytseva1, K.S. Mukhamedov4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Cryptococcal meningoencephalitis is an opportunistic mycosis. Earlier in medical practice single cases ofthe disease were encountered, now the problem becomes more and more urgent due to the increase in theHIV infection spread, as persons with impaired immune systems are affected. In most cases, cryptococcosisrefers to HIV-associated diseases. However, today there are unexplored clinical, virologic immunologicalaspects of HIV-associated cryptococcosis. The comparative rarity of the multi-organ nature of the lesion,the lack of objective clinical and laboratory data that allow to timely suspect and confirm a cryptococcalinfection, lead to errors in the diagnosis and treatment of this pathology. The main goal of our work is tostudy the prevalence of HIV-associated cryptococcosis, the clinical and laboratory features of HIV-associatedcryptococcosis in patients associated with inflammatory immune restoration syndrome to increase thediagnosis and treatment efficiency in Uzbekistan